GC–MS analysis underpins ethnomedicinal properties of Rhododendron flower brews from Singalila Himalaya highlighting the anticipated biosynthesis pathways of the bioactives - Soumya Majumder; Arindam Ghosh; Malay Bhattacharya (Discover Food)
Abstract Guras or Rhododendron wine and its Raksi are popular and therapeutic traditional drinks served in the rhododendron growing regions of the Himalayas; mainly in northern and north eastern part of India, Nepal and Indo-Nepal Singalila ridge. Earlier research showed that samples such as unfermented Guras decoction, wine and distilled liquor Raksi collected from Singalila ridge—the land of Guras exhibited potential bioactivities through various in vitro assays. In this follow-up research, GC–MS analysis was carried out that revealed responsible bioactive candidates which also exhibited correlations with reported physicochemical and biochemical properties. Abundance of phytochemicals including major compound quinic acid (34.97% peak area) was recorded in the unfermented decoction while the wine and Raksi were rich in bioactive fermented products i.e., metabolites of the fermenting microbes of the starter- Marcha. Furthermore, biosynthesis pathways of metabolites were proposed following microbial fermentation. Graphical Abstract